ANALISIS KEUNGGULAN KOMPARATIF USAHATANI PADI ORGANIK DI DESA SUKOREJO KECAMATAN SAMBIREJO KABUPATEN SRAGEN - Siregar, Duwi Majida Hayati; Suhartini; Widyawati, Wiwit (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
The agricultural sector that has the potential to be competitive, one of which is the food crop in rice commodities (Oryzae sativa) because rice is a leading commodity and the main food commodity in Indonesia. Indonesia can increase the competitiveness of rice with the emergence of